Створення концепту гри «садао – храм гармонії» - Базарна, П. А. (ХНУРЕ, 2024)
In today's world, everyone wants to find their own island of peace and harmony. This game is about harmony, its search and where it is. The name of the game to be developed is "Sadao - Temple of Harmony". The target audience for this game is 14+. Let's consider how the game will be built.
Keywords: концепт гри; «садао – храм гармонії»